The Difference Between Written And Spoken Grammar In Early Arabic Writing/ الاختلاف بين المكتوب والمنطوق نحويًّا في الكتابة العربية المبكِّرة - Aloufi, Sultan Awwad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research reveals a rare phenomenon in the history of Arabic writing that appeared in some of the writings that have reached us from the first and second centuries AH, which is the phenomenon of what the eloquent Arab writes contradicting what is spoken grammatically, which came in the context of a series of contradictions between what is written and what is spoken in Arabic writing. The research relied on discussing this phenomenon on two types of available written materials by the eloquent Arabs whose words are used as evidence: the Qur’anic script and early Islamic inscriptions. Following the descriptive analytical method, starting with defining the concept of that violation, presenting examples of it, and stating the limits of its occurrence in the Qur’anic script and early inscriptions, and discussing what clarifies it, such as stating its causes, effects, and the benefit of knowing it. The most prominent findings of the research are that this phenomenon was known in that era, which is proven in the inscriptions. As for the Qur’anic script, it did not occur overtly, but rather through different reading styles in which the readings were multiple, or through the belief of those devise places in the scripting of the Qur’an on that. One of the most prominent reasons for this phenomenon is the desire to write the word fixedly and leave the consideration of grammatical rules to the discerning and eloquent reader. This phenomenon disappeared after the development of the writing method and the spread of standard spelling rules. Still, it represents a feature of a distinctive historical stage in Arabic writing.